Problemas en la concepción de la “cadena variacional" de Koch y Oesterreicher y del diasistema lingüístico de Coseriu - Zimmermann, Klaus (El Colegio de México, 2024)
Coseriu’s three-dimensional conception of varieties does not take into account all the existing varieties: some do not fit into the established categories and the status of others is diffuse; given the multifactorial nature of the varieties, the diffusion can be attributed to several dimensions. His conception ignores the dynamic character of the social status ot the varieties in the course of evolution. This paper offers a deconstructivist analysis of essential points in Koch and Oesterreicher’s “variational chain”; a theorythat postulates a fixed orientation between the varieties of the diasystem. Cristicism is levelled at the mechanical character of its conception and at the rigidity of its orientation. A different vision (inspired by the energeia of Humboldt, including the role of the speaker) is proposed that considers varieties as a device that must be analyzed as a contact between varieties.